2023
DOI: 10.1029/2023gl105611
|View full text |Cite
|
Sign up to set email alerts
|

P and S Wave Anisotropic Tomography of the Banda Subduction Zone

Yuanyuan Hua,
Dapeng Zhao,
Yi‐Gang Xu

Abstract: In subduction zones with slab‐slab interactions, the pattern of mantle convection is very complex and still unclear. In this study, we jointly invert a large number of P and S wave arrival time data of local earthquakes for 3‐D isotropic and anisotropic velocity structures of the Banda subduction zone. Along the curved Banda arc, the subducting Indo‐Australian slab is detected clearly as a high‐velocity zone, and its azimuthal anisotropy changes along the arc strike, representing fossil anisotropy within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Recently, a novel tomographic technique has been developed to reveal tilting‐axis anisotropy, with the HSA freely orientated in 3‐D space (Z. Wang & Zhao, 2021). So far, this type of techniques has successfully revealed the presence of tilting HSA beneath the Japanese region (Z. Wang & Zhao, 2021) and its forearc area (Z. Wang et al., 2022), northern Fennoscandia (Munzarová et al., 2018), Central Mediterranean (Rappisi et al., 2022), and Cascadia subduction zone (Liang et al., 2023). These studies have demonstrated that the tilting‐axis anisotropy can reveal more complex 3‐D mantle flow by reconciling the contradictory assumptions of azimuthal and radial anisotropies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel tomographic technique has been developed to reveal tilting‐axis anisotropy, with the HSA freely orientated in 3‐D space (Z. Wang & Zhao, 2021). So far, this type of techniques has successfully revealed the presence of tilting HSA beneath the Japanese region (Z. Wang & Zhao, 2021) and its forearc area (Z. Wang et al., 2022), northern Fennoscandia (Munzarová et al., 2018), Central Mediterranean (Rappisi et al., 2022), and Cascadia subduction zone (Liang et al., 2023). These studies have demonstrated that the tilting‐axis anisotropy can reveal more complex 3‐D mantle flow by reconciling the contradictory assumptions of azimuthal and radial anisotropies.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation of the intraslab anisotropy is preferred orientation of hydrated faults, which are developed in the upper part of slab due to plate‐bending prior to subduction (Faccenda et al., 2008, 2009). The trench‐parallel faults can cause trench‐parallel FVPs in the upper portion of the subducting slab, which has been observed in other subduction zones (e.g., Han et al., 2016; Liang et al., 2023; Wang, Zhao, & Chen, 2022). However, our Vp tomographic results indicate that the anisotropy in most parts (Regions E, G, and H) within the subducting Australian slab does not seem to match the characteristics of the FVPs caused by the hydrated faults, except for the local area between 120°E and 128°E beneath Timor Island (Region F).…”
Section: Discussionmentioning
confidence: 82%
“…Shear‐wave splitting measurements (Wang & He, 2020) and azimuthal anisotropic tomography (Hua et al., 2023) have observed that FVDs in the back‐arc region rotate from trench‐normal in the west (Java) to trench‐parallel in the east (Banda), reflecting a complex mantle flow pattern associated with the slab geometry. Under the assumption of a tilting hexagonal symmetry axis, the 3‐D Vp anisotropic model we obtained reasonably matches the features reported by the previous studies (Hua et al., 2022; Wang & He, 2020) and provides additional information that was not reported before, because we are able to better constrain 3‐D mantle flows and intraslab anisotropy.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations